Psychosocial Factors in End-Stage Kidney Disease Patients at a Tertiary Hospital in Australia - Charan Bale; Alexandra Douglas; Dev Jegatheesan; Linh Pham; Sonny Huynh; Atul Mulay; Dwarakanathan Ranganathan (International Journal of Nephrology)
Aim. This study seeks to review the psychosocial factors affecting patients with end-stage kidney disease (ESKD) from a tertiary hospital in Australia. Methods. We audited patients with ESKD, referred to social work services from January 2012 to December 2014. All patients underwent psychosocial assessments by one, full-time renal social worker. Patient demographics, cumulative social issues, and subsequent interventions were recorded directly into a database. Results. Of the 244 patients referred, the majority were >60 years (58.6%), male (60.7%), born in Australia (62.3%), on haemodialysis (51.6%), and reliant on government financial assistance (88%). Adjustment issues (41%), financial concerns (38.5%), domestic assistance (35.2%), and treatment nonadherence (21.3%) were the predominant reasons for social work consultation. Younger age, referral prior to start of dialysis, and unemployment were significant independent predictors of increased risk of adjustment issues (p=0.004, <0.001, and =0.018, resp.). Independent risk factors for treatment nonadherence included age and financial and employment status (p=0.041, 0.052, and 0.008, resp.). Conclusion. Psychosocial and demographic factors were associated with treatment nonadherence and adjustment difficulties. Additional social work support and counselling, in addition to financial assistance from government and nongovernment agencies, may help to improve adjustment to the diagnosis and treatment plans as patients approach ESKD.